GE_GERICHTE P/10121/2022 vom 9. Februar 2025 - GE Cour de justice (2025)
ESCROQUERIE;FAUX INTELLECTUEL DANS LES TITRES;LOI COVID-19;PRÊT DE CONSOMMATION | CP.146; CP.251; CPP.9; CPP.329; CPP.333; CPP.430